Simulação com pacientes padronizados: habilidades de comunicação em saúde do estudante de enfermagem - Fernanda dos Santos Nogueira de Góes; Natália Del\u2019 Angelo Aredes; Cristina Yuri Nakata Hara; Luciana Mara Monti Fonseca; Suzanne Hetzel Campbell (Universidade Federal do Ceará, 2017)
Objective: to identify and measure nursing student's communication skills in health using simulation with standardized patients. Methods: descriptive, cross-sectional study carried out with 16 students of the last year of the nursing undergraduate course. The simulation focused on requesting authorization from the patient/ family to perform venipuncture. During the simulation, all the students were evaluated through the Health Communication Assessment Tool . Results: of the 22 items of the tool, 18 reached agreement higher than 50.0%. Of the 16 participants, 14 (87.5%) were assessed as being able to communicate in more than 50.0% of the statements. Conclusion: students' communication was satisfactory; there are gaps related to the emotional aspects of the patient and the family, manifesting the need to reinforce communication in the nursing curriculum.